A liberal carbohydrate allowance in the dietary management of five patients with diabetes mellitus - Alvarez, Amelita Cruz 1944-
Most hospitals in Manila and vicinity have pattered diets for patients with diabetes mellitus after those recommended by the American Diabetes Association, with carbohydrates allowance of 40-60% of non-protein calories. These levels are lower than the average carbohydrate intake of a Filipino which is 88% of non-protein calories as calculated from findings of nutrition surveys made in eight regions of the Philippines by the Food and Nutrition Research Center. In an attempt to draw attention to the idea of providing the Filipino diabetic patient a higher carbohydrate allowance than he had previously been prescribed, five hospitalized diabetic patients were given isocaloric diets with carbohydrates comprising 50% and 70% of non-protein calories. Four patients receiving a constant dosage of medication, regardless of whether they had oral drugs or insulin, showed a downward trend of fasting blood sugar (FBS) to normal levels on the increased carbohydrate diet. The patient managed by dietary means alone showed a rise in FBS with increased carbohydrate intake. However, he had only one FBS determination while on each type of diet. The experimental diet of carbohydrate as 70% of non-protein calories was more acceptable to all five subjects in terms of quantities of each food group served, compared to the control diet of 50%. In view of the tendency of their FBS levels to go down to normal on the carbohydrate intake of 70% of non-protein calories, it appears that for the four diabetic subjects receiving medication, this increased carbohydrate level may be used as a framework in planning diets.